Sosialisasi Digital Marketing Dalam Meningkatkan Pendapatan UMKM Di Desa Basilam Baru Kecamatan Muara Tais-II Kabupaten Tapanuli Selatan - Alwendi, Alwendi (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The Awakened Indonesia UKM program provides a solution to overcome this problem, namely a solution to technological capacity constraints by procuring production machines such as cutting machines, drill presses, compressor machines, workbenches, and wheelbarrows. Solution to marketing/distribution and managerial constraints by designing and manufacturing an Android-based Management Information System (SIMBA) that can help partners use database-based information and communication technology so that partners can provide knowledge and expertise to carry out marketing activities (product updates, online sales, online transactions, distribution arrangements), inventory activities (management of inventories based on online purchase orders), and assist in preparing the company's income statement. Besides that, it also offers marketing media using neon box boards. The solutions provided can help increase the productivity of FortunaHandycraft SMEs in terms of production, digital marketing and managerial.